Psychometric properties of the Academic Major Satisfaction Scale (AMSS) in Brazilian College Students - Silva Soares, Ana Karla (2021)
Academic satisfaction has been studied from different perspectives that considerate distinct ways of measurement. However, the plurality of evaluated facets prevents a more parsimonious assessment of the general students’ academic satisfaction. In the article, we aimed to provide psychometric evidence of the validity and reliability for the AMSS in Brazil in two studies (N = 893). In Study 1, an exploratory factor analysis and item parameters (Item Response Theory) support the one-factor solution and the suitability of the six items. Moreover, evidence for factorial invariance across gender and convergent validity with the PANAS and with the SWLS was also presented in Study 2. In conclusion, the present paper provides evidence of the adequacy of the AMSS to evaluate global satisfaction with the academics course in Brazil.